English for Tourism in Iceland: ESP Course Design Development for the Upper Secondary Level - Kristín Jónasdóttir 1983- (2017)
In the last five years, the Icelandic tourism industry has expanded enormously as numbers of foreign visitors have rapidly increased each year. Already, thousands of Icelanders are working in the Icelandic tourism sector which plays a large part of the country’s economy. Many of these workers have not received any specific training in tourism studies. Some of them are upper-secondary students who only work during the summer months, the rest was recruited as the need for tourism employers became essential to cater to the massive amounts of tourist arrivals. However, the ongoing growth and scope of the Icelandic tourism sector calls for more professional training. Alongside the expansion in tourism, Icelandic universities and upper-secondary schools began offering courses in tourism studies, but specific tourism English teaching and communication skills training is still lacking. This thesis presents an outline for an English for Tourism in Iceland course for the upper-secondary level. The course design is based on the Icelandic National Curriculum Guide for upper-secondary schools and the ESP method, which teaches specific English according to learners’ interests and future need. A study was conducted, in which tourism professionals and upper-secondary students are asked about their views on this type of course, as well as which material it should include. Results show both groups think it is important to include materials with classic information about Iceland and put them in context with important tourism materials. Both groups feel it is important to train students’ listening and speaking skills, cross-cultural communication skills and English tourism vocabulary. ESP, English for Specific Purposes, Upper-secondary school, Tourism English, Course Design.